Factores motivacionales asociados al rendimiento de un grupo de deportistas de una escuela de voleibol en la ciudad de Cartago (2024)
The present research is carried out with the objective of describing the characteristics of the motivational factors of a group of young athletes belonging to the popular volleyball school of the Zaragoza district of the municipality of Cartago Valle del Cauca, this group, like any other in the country reflects the idiosyncrasy of the territory both at the regional and national level.